Pengaruh Rasio Tepung Ampas Kelapa dan Singkong Parut Terhadap Sifat Kimia dan Sensoris Kue Klenyem - Septiana, Ika; Trisna Darmayanti, Luh Putu; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 1 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i01.p14, 2021)
This research aims to determine the comparison effect of coconut pulp flour with grated cassava on the characteristics of klenyem cake, and to find out the exact ratio of coconut flour and grated cassava so as to produce the best characteristics of klenyem cake. The experimental design used Completely Randomized Design (CRD) with treatment of coconut pulp flour and grated cassava ratio consist 6 levels : 20% : 80%; 30% : 70%; 40% : 60; 50% : 50%; 60% : 40%; 70% : 30%. Each treatment was repeated 3 times so obtained 18 experimental units. The parameters observed were water content, ash content, protein content, fat content, carbohydrate content, crude fiber content and the sensory test of the klenyem cake.The data obtained were using Analysis of Variance (ANOVA) and if the significant effect to the variables, followed by The Duncan Multiple Range Test (DMRT). The results showed that the comparison of coconut pulp flour and grated cassava have a significant effect on the water content, ash content, protein content, fat content, carbohydrate content, crude fiber content, color and texture (scoring), aroma, taste and overall acceptance (hedonic). Comparison of coconut pulp flour with grated cassava 40%: 60% has been able to produce the best characteristics of klenyem cake. The parameter results of 40% coconut pulp flour with 60% grated cassava that is water content 32.54%, ash content 1.78%, protein content 2.85%, fat content 33.72%, carbohydrate content 33.61%, crude fiber content 21.62%, yellow color, soft texture, aroma liked, taste liked and overall acceptance liked.